Peran mediasi work life balance di antara work from home dan kepuasan kerja - Dianawati Suryaningtyas; Sri Wilujeng; Riril Mardiana Firdaus (MBR (Management and Business Review), 2022)
The purpose of the study was to determine the effect of work from home on work-life balance, work-life balance on job satisfaction, work from home on job satisfaction and work from home on job satisfaction mediated by work-life balance. Work from home is measured by management culture, technical support, supervisor trust, support from the Human Resource department, financial support, training, job features, personal work preferences, and household factors. Work-life balance is measured by time balance, engagement balance, and overall. Job satisfaction is measured by the achievement of satisfaction. Data were analyzed using Partial Least Square (PLS). The results of the analysis show that work from home has an effect on work-life balance, work-life balance has an effect on job satisfaction, and work from home has no effect on job satisfaction. Work-life balance contributes to mediating the impact of remote employment on job satisfaction. It is suggested that this research be developed in a different setting and that more samples and other variables be used.